IMPLEMENTATION OF ISLAMIC EDUCATION IN THE ESTABLISHMENT OF NOBLE CHARACTER OF CHILD PRISONERS IN SPECIAL CHILD DEVELOPMENT INSTITUTION (LPKA) CLASS II MAROS - Harisman, Teguh; Siraj, Arifuddin; Naro, Wahyuddin (Program Pascasarjana, UIN Alauddin Makassar, 2021)
This research focuses attention on the implementation of the program of fostering the noble character of child prisoners by implementing the concept of Islamic education. This research is classified as a type of descriptive qualitative research with research locations at the Special Development Institute for Children (LPKA) located in the maros district. The results of this study showed that LPKA Class II Maros has carried out coaching with the concept of Islamic education through programs including: 1) Personality coaching, 2) Physical coaching, 3) Coaching intellectual abilities, 4) law awareness coaching, 5) Coaching skills.